The effectiveness of job embeddedness in turnover studies: A meta-analysis - Lee, JongHyun; Shin, KangHyun; Baeck, SeungGeun; Heo, ChangGoo (Korean Journal of Industrial and Organizational Psychology, 2014)
The main objective of this study is to investigate the strength of the relationship among job embeddedness, organizational commitment, job satisfaction, and turnover intentions among Korean employees using meta-analytic methods with theoretical rationale. The results from meta-analysis of 44 Korean studies are as follows. First, the true-score correlations among on-the-job embeddedness, fit to organization, organization-related sacrifice, and turnover intention are -.569, -.462, -.414 each (k = 14-30, N = 4657-8299); the 95% CIs and 80% CVs for all relationships had no zero. Second, the true-score correlations among on-the-job embeddedness, three sub-factors, and work-related attitudes (affective commitment, job satisfaction) are all positively correlated and the 95% CIs and 80% CVs for all relationships had no zero. Third, the magnitude of true-score relationship between on-the-job embeddedness and work-related variables is somewhat stronger in this meta-analysis than in counterpart studies in western countries. Finally, estimating the incremental validity of on-the-job embeddedness using meta-analytic structural equation model, on-the- job embeddedness remains negatively related with turnover intention, after affective commitment and job satisfaction are controlled. This meta-analytic findings contribute to understanding of the relationships among job embeddedness and work-related variables among Korean employees. Future studies should attempt to overcome the limitations of this study such as lack of information related to demographics. Further, more primary studies are needed since there were very few available studies on actual turnover and off-the-job embeddedness. Hopefully, this study will be a good guide for the future Korean studies on job embeddedness.